Lithium metal negative electrode material and preparation method thereof, lithium metal negative electrode plate and lithium metal battery

By using a dense and flexible artificial SEI film generated by bi-in-situ reaction in the lithium metal negative electrode material, the problem of generating an uneven SEI film when the lithium metal negative electrode comes into contact with the organic electrolyte is solved, and uniform deposition of lithium ions and extension of battery cycle life is achieved.

CN119725427APending Publication Date: 2025-03-28JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411644405.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the lithium metal negative electrode comes into contact with the organic electrolyte, it will spontaneously react sideways, generating uneven and unstable solid electrolyte interface masks (SEIs), resulting in uneven deposition of lithium ions, producing dead lithium and lithium dendrites, causing safety problems and reducing the cycle life of the battery.

Method used

A lithium metal negative electrode material with an artificial SEI film generated by a bi-in-situ reaction includes a lithium metal matrix, a functional layer and a hybrid layer. The functional layer consists of substance A (such as zinc silicate) and EP compounds. The mixed layer includes lithium-philic components, continuous lithium-ion components and EP compounds to form a dense and flexible SEI film that covers the negative electrode of lithium metal and shields the corrosion of lithium metal by the electrolyte.

Benefits of technology

It realizes uniform deposition of lithium ions, inhibits dendrite nucleation and growth, reduces surface resistance, improves electrochemical compatibility, extends the cycle life of the battery, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725427A_ABST
    Figure CN119725427A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium metal negative electrode material and a preparation method thereof, a lithium metal negative electrode plate and a lithium metal battery. The lithium metal negative electrode material comprises a lithium metal matrix and a functional layer arranged on the surface of the lithium metal matrix, wherein the functional layer comprises a substance A and an EP compound; the substance A comprises M-containing weak acid salt and / or M-containing organic salt, and M is Zn and / or Mg; the copolymer monomer of the EP compound comprises a compound B1 and a compound B2, the compound B1 is PEGDA, and the compound B2 comprises at least one of VC, CEC and DTD. The artificial SEI film of the lithium metal negative electrode material has a compact structure, has good flexibility and elasticity, can completely cover a lithium metal negative electrode, shields corrosion of an electrolyte to lithium metal, promotes uniform deposition of lithium ions while reducing the surface resistance, has good electrochemical compatibility with the lithium metal negative electrode, is not easy to reduce, and can be applied to the lithium metal negative electrode. The stability is kept in long-term circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to lithium metal negative electrode materials and preparation methods thereof, lithium metal negative electrode sheets and lithium metal batteries. Background Art

[0002] In the next generation of lithium batteries, lithium metal anode is regarded as the focus of lithium metal battery development. Lithium metal anode has extremely low electrochemical potential (-3.040V, to standard hydrogen electrode) and extremely high theoretical specific capacity (3860mAh g -1 ), becoming a key material in lithium metal batteries. However, lithium metal anodes face a series of challenges, one of which is that they spontaneously react with organic electrolytes to form a solid electrolyte interface (SEI) on the surface of lithium metal. Unfortunately, the SEI generated in situ during the cycle is mostly uneven, and the internal mechanical structure is unstable and has limited flexibility. + ) will be unevenly deposited on the surface of the lithium negative electrode during migration, resulting in the formation of dead lithium and lithium dendrites. The sharp lithium dendrites will pierce the diaphragm, causing the positive and negative electrodes to short-circuit, thus causing serious safety problems. Moreover, during the process of lithium ion insertion and extraction, the SEI film expands in volume, causing the SEI film to break, and the bulk structure re-contacts with the electrolyte, regenerating the SEI film, which not only consumes the electrolyte, but also thickens the SEI film and increases the R SEI , increasing polarization and reducing cycle life. At the same time, due to the uneven thickness of the SEI film, the local current density is different, the lithium ion deposition rate is inconsistent, and a loose and porous "lithium sponge" is formed on the surface of the lithium metal, which increases the thickness of the battery cell and reduces the cycle performance. In addition, the naturally generated SEI film has poor electrochemical stability and is prone to oxidation at high voltage.

[0003] At present, the common solution is to add film-forming additives to the electrolyte, such as fluorinated ethylene carbonate (FEC), lithium nitrate (LiNO3), vinylene carbonate (VC), etc., to form a stable artificial SEI layer on the electrode surface. So far, various artificial SEIs have been successfully used in the modification of lithium metal anodes, including inorganic materials (for example, lithium phosphate Li3PO4, lithium fluoride LiF, silicon dioxide SiO2 and aluminum oxide Al2O3, etc.) and organic polymers (for example, polyacrylic acid PAA, polydimethylsiloxane PDMS, polyethylene glycol PEG, etc.). Among them, Li + The electrical conductivity is usually high, but the elasticity is poor, and the inorganic particles cannot densely cover the lithium metal negative electrode, making it difficult to shield the electrolyte from corroding the lithium metal. Summary of the invention

[0004] In view of this, the present invention provides a lithium metal negative electrode material and a preparation method thereof, a lithium metal negative electrode sheet and a lithium metal battery. The artificial SEI film of the lithium metal negative electrode material has a dense structure, and has flexibility and good elasticity, can completely cover the lithium metal negative electrode, shield the corrosion of the electrolyte to the lithium metal, promote the uniform deposition of lithium ions while reducing the surface resistance, has good electrochemical compatibility with the lithium metal negative electrode, is not easily reduced, and remains stable in long-term cycles.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a lithium metal negative electrode material, the lithium metal negative electrode material comprising:

[0007] (a) Lithium metal matrix;

[0008] (b) a functional layer, the functional layer is disposed on the surface of the lithium metal substrate, and the functional layer includes substance A and EP compound;

[0009] Substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn (zinc) and / or Mg (magnesium);

[0010] The copolymer monomers of the EP compound include a B1 compound and a B2 compound, wherein the B1 compound is polyethylene glycol diacrylate (PEGDA), and the B2 compound includes at least one of vinylene carbonate (VC), chloroethylene carbonate (CEC), and divinyl sulfate (DTD).

[0011] Preferably, substance A includes at least one of silicate, acetate, citrate and lactate.

[0012] Preferably, substance A includes at least one of zinc silicate, magnesium silicate, zinc acetate, magnesium acetate, zinc citrate, magnesium citrate, zinc lactate, and magnesium lactate.

[0013] More preferably, substance A is zinc silicate.

[0014] In an embodiment of the present invention, the lithium metal negative electrode material further includes a mixed layer, which is disposed between the lithium metal matrix and the functional layer, and the mixed layer includes a lithium-philic component, a continuous lithium ion-conducting component and an EP compound.

[0015] In an embodiment of the present invention, the lithium-philic component includes M metal and Li-M alloy, wherein M is Zn and / or Mg.

[0016] In an embodiment of the present invention, the continuous lithium ion conducting component includes a weak acid salt and / or an organic salt of lithium, Li2O and LiOH.

[0017] Preferably, in the mixed layer, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the EP compound is (5-50):(5-50):1.

[0018] Preferably, the lithium-philic component, the continuous lithium-ion-conducting component and the EP compound are combined in such a way that the lithium-philic component and the continuous lithium-ion-conducting component are encapsulated by the EP compound.

[0019] Preferably, the thickness of the functional layer is 20 to 1000 nm.

[0020] Preferably, the thickness of the mixed layer is 10 to 200 nm.

[0021] Preferably, the thickness ratio of the functional layer to the mixed layer is (2-100):(1-20) 。

[0022] Preferably, in the functional layer, the mass ratio of substance A to compound EP is (1-10):1.

[0023] Preferably, the A substance and the EP compound are combined in such a way that the EP compound encapsulates the A substance.

[0024] In the embodiment of the present invention, the mass of the lithium metal matrix is ​​recorded as n1, the mass of the A substance is recorded as n2, and the mass of the EP compound is recorded as n3. n1, n2, and n3 satisfy the following relationship:

[0025] 50≤n1 / (n2+n3)≤300.

[0026] In a second aspect, the present invention provides a method for preparing a lithium metal negative electrode material, comprising the following steps:

[0027] S1, mixing substance A, compound B1, compound B2, a photoinitiator and an organic solvent to obtain a dispersion;

[0028] Substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg;

[0029] Compound B1 is polyethylene glycol diacrylate (PEGDA);

[0030] The B2 compound includes at least one of vinylene carbonate (VC), ethylene monochloride carbonate (CEC), vinylene sulfate (DTD), and ethylene glycol sulfate (DTD);

[0031] S2, in an inert gas atmosphere, applying the dispersion to the surface of the lithium metal substrate, subjecting the substrate to ultraviolet light polymerization treatment, polymerizing the B1 compound and the B2 compound into an EP compound, and then subjecting the substrate to a standing treatment to obtain a lithium metal negative electrode material.

[0032] Preferably, the mass ratio of substance A, compound B1 and compound B2 is (10-50):(5-10):(1-5).

[0033] Preferably, the photoinitiator 、 The mass ratio of the B1 compound to the B2 compound is (10-50):(5-10):(1-5).

[0034] Preferably, the temperature of the ultraviolet light polymerization treatment is -50°C to -30°C, and the time of the ultraviolet light polymerization treatment is 5 to 15 minutes.

[0035] Preferably, the temperature of the static treatment is 10°C to 30°C, and the time of the static treatment is 10 to 20 hours.

[0036] In a third aspect, the present invention provides a lithium metal negative electrode sheet, which includes the above-mentioned lithium metal negative electrode material and / or the lithium metal negative electrode material prepared by the above-mentioned preparation method.

[0037] In a fourth aspect, the present invention provides a lithium metal battery, which includes the above-mentioned lithium metal negative electrode sheet.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The lithium metal negative electrode material provided by the present invention is a lithium metal negative electrode material with an artificial SEI film generated by a dual in-situ reaction, and the lithium metal negative electrode material includes a lithium metal matrix and a functional layer; the functional layer is arranged on the surface of the lithium metal matrix, and the functional layer includes substance A and EP compound. Further, the lithium metal negative electrode material also includes a mixed layer arranged between the lithium metal matrix and the functional layer, and the mixed layer includes a lithium-philic component, a continuous lithium ion-conducting component and an EP compound. Both the functional layer and the mixed layer are artificial SEI films of the lithium metal negative electrode material.

[0040] Among them, the EP compound in the functional layer and the EP compound in the mixed layer are components of the artificially synthesized SEI film of the present invention, and have the ability of lithium ions to pass through. On the other hand, this compound is an organic compound and has electronic insulation, so that the lithium metal negative electrode material has good electronic insulation. At the same time, this compound has ionic conductivity, which can realize the rapid migration of ions between the lithium metal negative electrode and the electrode, and at the same time inhibit the direct reduction of lithium ions on the interface, thereby inhibiting the nucleation and growth dynamics of dendrites;

[0041] The lithium-philic component and the continuous lithium-ion-conducting component in the mixed layer are formed by an in-situ reaction between substance A and the surface of the lithium metal matrix to generate a lithium-philic component including M metal and Li-M alloy (where M is Zn and / or Mg), and a continuous lithium-ion-conducting component including a lithium weak acid salt and / or organic salt, Li2O and LiOH. Among them, the lithium-philic component can induce uniform deposition of lithium ions without generating lithium dendrites; the continuous lithium-ion-conducting component can reduce R SEI (impedance when lithium ions pass through SEI membrane), accelerating the redox reaction at the negative electrode interface. Since the nanoparticle structure of substance A with low crystallinity has a tendency to stack, effective in-situ reaction transformation occurs, forming a dense structure of the lithiated product, so that the final product D including the lithium-philic component and the continuous lithium-ion conducting component 90 <3nm, including the porosity of the product layer of the functional layer and the mixed layer <5%. The naturally formed SEI film is loose and easy to fall off during the charge and discharge process, while the artificially generated in-situ grown SEI film (including the product layer of the functional layer and the mixed layer) of the present invention has a dense structure, making the SEI film thin and strong, not easy to fall off, and reducing the loss of active lithium;

[0042] The lithium-philic component and the continuous lithium-ion-conducting component in the mixed layer of the lithium metal negative electrode material provided by the present invention are generated by spontaneous oxidation-reduction reaction between substance A and the surface of the lithium metal matrix (lithium is more active than metal M, so when substance A is applied to the surface of lithium metal, oxidation-reduction reaction can occur spontaneously). Therefore, the artificially generated SEI film (including the product layer of the functional layer and the mixed layer) of the present invention has good electrochemical compatibility with the lithium metal negative electrode, is not easily reduced, and remains stable in long-term cycles;

[0043] In the lithium metal negative electrode material of the present invention, since the EP compound acts as a suspending agent in the slurry preparation process and acts as a binder after in-situ polymerization, and the A substance also acts as a binder after the in-situ reaction, the lithium-philic component and the continuous lithium ion-conducting component are staggered with the in-situ polymerized EP compound (polymer solid electrolyte membrane) under ultraviolet light irradiation, and since the EP compound has flexibility and good elasticity, the artificially generated SEI film of the present invention has flexibility and compactness, which can reduce the surface resistance and promote the uniform deposition of lithium ions;

[0044] In the preparation method of the lithium metal negative electrode material of the present invention, substance A can adjust the distribution of unsaturated bonds of the polymer (EP compound) inside the slurry, can quickly stimulate the unsaturated bond polymerization of the polymer monomers (B1 compound and B2 compound), shorten the polymerization reaction time, and improve the efficiency of large-scale production of artificial SEI film. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1: Schematic diagram of the structure of the lithium metal negative electrode material of the present invention, wherein the functional layer and the mixed layer constitute the EP@Zn2SiO4 artificial SEI film.

[0046] Figure 2 : SEM image of the EP@Zn2SiO4 artificial SEI film of the present invention.

[0047] The reference numerals are: 1 is a lithium metal matrix; 2 is a mixed layer; and 3 is a functional layer. DETAILED DESCRIPTION

[0048] The present invention discloses a lithium metal negative electrode material and a preparation method thereof, a lithium metal negative electrode sheet and a lithium metal battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0049] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.

[0050] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0051] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0052] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0053] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0054] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0055] Specifically, the present invention adopts the following technical solutions:

[0056] In a first aspect, the present invention provides a lithium metal negative electrode material, the lithium metal negative electrode material comprising:

[0057] (a) Lithium metal matrix;

[0058] (b) a functional layer, the functional layer is disposed on the surface of the lithium metal substrate, and the functional layer includes substance A and EP compound;

[0059] Substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn (zinc) and / or Mg (magnesium);

[0060] The copolymer monomers of the EP compound include a B1 compound and a B2 compound, wherein the B1 compound is polyethylene glycol diacrylate (PEGDA), and the B2 compound includes at least one of vinylene carbonate (VC), chloroethylene carbonate (CEC), and divinyl sulfate (DTD).

[0061] In the embodiment of the present invention, the carbon-carbon double bonds of the B1 compound and the B2 compound are disconnected and bonded to form a copolymer EP compound.

[0062] Preferably, substance A includes at least one of silicate, acetate, citrate and lactate.

[0063] Preferably, substance A includes at least one of zinc silicate, magnesium silicate, zinc acetate, magnesium acetate, zinc citrate, magnesium citrate, zinc lactate, and magnesium lactate.

[0064] More preferably, substance A is zinc silicate. Compared with other types of substance A, zinc silicate has a redox potential and metal activity suitable for lithium metal battery systems, so that zinc silicate reacts in situ with the surface of lithium metal to generate Zn metal and Li x Zn y Lithium-philic components of alloys and Li x SiO y The continuous lithium-ion conducting components of Li2O and LiOH. The zinc silicate nanoparticle structure with low crystalline characteristics has a tendency to stack, which enables effective in-situ reaction transformation to occur and form a dense structure of the lithiated product.

[0065] In an embodiment of the present invention, the EP compound is at least one of a copolymer of polyethylene glycol diacrylate and vinyl carbonate (PEGDA-co-VC copolymer), a copolymer of polyethylene glycol diacrylate and monochlorocarbonate (PEGDA-co-CEC copolymer), and a copolymer of polyethylene glycol diacrylate and vinyl sulfate (PEGDA-co-DTD copolymer). The EP compound is a synthetic SEI membrane component of the present invention, and has the ability of lithium ions to pass through. On the other hand, this compound is an organic compound and has electronic insulation, so that the lithium metal negative electrode material has good electronic insulation. At the same time, this compound has ionic conductivity, which can realize the rapid migration of ions between the lithium metal negative electrode and the electrode, and inhibit the direct reduction of lithium ions at the interface, thereby inhibiting the nucleation and growth dynamics of dendrites. At the same time, since the EP compound acts as a suspending agent in the slurry preparation process and acts as a binder after in-situ polymerization, and substance A also acts as a binder after the in-situ reaction, the lithium-philic component and the continuous lithium-ion-conducting component generated by substance A are staggered with the in-situ polymerized EP compound (polymer solid electrolyte membrane) under ultraviolet light irradiation. Moreover, since the EP compound has flexibility and good elasticity, the artificially generated SEI film of the present invention has flexibility and density at the same time, which can reduce the surface resistance while promoting the uniform deposition of lithium ions.

[0066] In an embodiment of the present invention, the lithium metal negative electrode material further includes a mixed layer, which is disposed between the lithium metal matrix and the functional layer, and the mixed layer includes a lithium-philic component, a continuous lithium ion-conducting component, and an EP compound. Since lithium is more active than M metal, a redox reaction can occur spontaneously when substance A is applied to the surface of the lithium metal matrix, and substance A reacts with lithium metal to generate a lithium-philic component and a continuous lithium ion-conducting component. Among them, the lithium-philic component can induce uniform deposition of lithium ions without generating lithium dendrites; the continuous lithium ion-conducting component can reduce R SEI (impedance when lithium ions pass through SEI film), accelerating the redox reaction at the negative electrode interface. Since the nanoparticle structure of substance A with low crystallinity has a tendency to stack, an effective in-situ reaction transformation occurs, forming a dense structure of the lithium product, so that the final product (including the lithium metal negative electrode material of the functional layer, the mixed layer and the lithium metal matrix) including the lithium-philic component and the continuous lithium-ion conducting component is D 90 <3nm, and the porosity of the product layer including the functional layer and the mixed layer is <5%. The naturally formed SEI film is loose and easy to fall off during the charge and discharge process, while the artificially generated SEI film (including the product layer of the functional layer and the mixed layer) of the present invention has a dense structure, making the SEI film thin and strong, reducing the loss of active lithium. At the same time, the artificially generated SEI film of the present invention has good electrochemical compatibility with the lithium metal negative electrode, is not easily reduced, and remains stable in long-term cycles.

[0067] In an embodiment of the present invention, the lithium-philic component includes M metal and Li-M alloy, wherein M is Zn and / or Mg.

[0068] In an embodiment of the present invention, the M metal in the lithiophilic component includes Zn metal and / or Mg metal.

[0069] In an embodiment of the present invention, the Li-M alloy in the lithium-philic component includes a Li-Zn alloy and / or a Li-Mg alloy.

[0070] In the present invention, the "continuous lithium ion conducting component" is equivalent to the SEI film, has the characteristics of a solid electrolyte, is an electronic insulator and Li + Excellent conductor, Li + It can be freely inserted and extracted through this layer. In an embodiment of the present invention, the continuous lithium ion conducting component includes a weak acid salt and / or an organic salt of lithium, Li2O and LiOH.

[0071] In the embodiment of the present invention, the weak acid salt or organic salt of lithium in the continuous lithium ion conducting component comprises lithium silicate (Li x SiO y , wherein 2≤x≤8, 3≤y≤6, such as Li8SiO6, Li4SiO4, Li2SiO3, etc.), at least one of lithium acetate, lithium citrate, and lithium lactate.

[0072] Preferably, in the mixed layer, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the EP compound is (5-50):(5-50):1. Exemplarily, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the EP compound is any value in 5:5:1, 10:10:1, 15:15:1, 20:20:1, 25:25:1, 30:30:1, 35:35:1, 40:40:1, 45:45:1, 50:50:1 or any value in the range of any two of the above values. When the proportion of the lithium-philic component and the continuous lithium-ion-conducting component is too large, the impedance will increase; when the proportion of the lithium-philic component and the continuous lithium-ion-conducting component is too small, it will not protect the lithium metal, resulting in lithium loss.

[0073] Preferably, in the mixed layer, the lithium-philic component, the continuous lithium-ion-conducting component and the EP compound are combined in such a way that the EP compound encapsulates the lithium-philic component and the continuous lithium-ion-conducting component. The EP compound has the function of a binder, and the lithium-philic component and the continuous lithium-ion-conducting component can be encapsulated by the EP compound by simple mechanical mixing.

[0074] Preferably, the thickness of the functional layer is 20 to 1000 nm. Exemplarily, the thickness of the functional layer is any value among 20 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or any value within the range of any two of the above values. When the functional layer is too thick, the energy density of the lithium metal battery will be lost and the lithium ion transmission efficiency will be reduced; when the functional layer is too thin, it will not be able to protect the lithium metal matrix.

[0075] Preferably, the thickness of the mixed layer is 10 to 200 nm. Exemplarily, the thickness of the mixed layer is any value among 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, or any value within the range of any two of the above values. When the mixed layer is too thick, the energy density of the lithium metal battery will be lost and the lithium ion transmission efficiency will be reduced; when the mixed layer is too thin, it will not be able to protect the lithium metal matrix.

[0076] Preferably, the thickness ratio of the functional layer to the mixed layer is (2-100):(1-20) 。 Exemplarily, the thickness ratio of the functional layer to the mixed layer is any value in 1:10, 1:8, 1:6, 1:4, 1:2, 1:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1 or any value in the range of any two of the above values. When the thickness ratio of the functional layer to the mixed layer is controlled at (2 to 100): (1 to 20), the comprehensive effects of the functional layer and the mixed layer can be taken into account. On the one hand, the EP compound in the functional layer and the EP compound in the mixed layer are components of the artificially synthesized SEI film of the present invention, which have electronic insulation, so that the lithium metal negative electrode material has good electronic insulation. At the same time, this compound has ionic conductivity, which can realize the rapid migration of lithium ions between the lithium metal negative electrode and the electrode, and at the same time inhibit the direct reduction of lithium ions at the interface, thereby inhibiting the nucleation and growth dynamics of dendrites. On the other hand, the lithium-philic components in the mixed layer can induce uniform deposition of lithium ions without producing lithium dendrites; the continuous lithium-ion-conducting components can reduce R SEI (The impedance of lithium ions passing through the SEI membrane) accelerates the redox reaction at the negative electrode interface.

[0077] Preferably, in the functional layer, the mass ratio of substance A to the EP compound is (1-10):1. Exemplarily, the mass ratio of substance A to the EP compound is any value among 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value within the range of any two of the above values. If the ratio is too large, the proportion of EP compound is too low, and substance A cannot be wrapped, which affects the generation of continuous lithium ion conductive components; if the ratio is too small, the ionic conductivity of the functional layer is too low, resulting in increased resistance and polarization, and reaching the cut-off voltage in advance, which further leads to reduced capacity and affects the first effect. Preferably (1-3):1.

[0078] Preferably, in the functional layer, the combination of substance A and EP compound is that EP compound encapsulates substance A. In the embodiment of the present invention, substance A shows positive charge and large surface energy; hydroxyl group and carbon oxygen double bond of EP compound show negative charge and can act as a binder; coordination bond is formed between substance A and EP compound. Therefore, encapsulation of substance A by EP compound can be achieved by simple mechanical mixing.

[0079] In an embodiment of the present invention, the mass of the lithium metal matrix is ​​recorded as n1, the mass of the A substance is recorded as n2, and the mass of the EP compound is recorded as n3. n1, n2, and n3 satisfy the following relationship: 50≤n1 / (n2+n3)≤300. Exemplarily, the ratio of n1 / (n2+n3) is any value among 50, 60, 80, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300 or any value within the range of any two of the above values. If the ratio of n1 / (n2+n3) is too large, the lithium metal matrix cannot be protected due to the small proportion of the functional layer; if the ratio of n1 / (n2+n3) is too small, the energy density of the lithium metal battery will be lost and the lithium ion transmission efficiency will be reduced.

[0080] In an embodiment of the present invention, the lithium metal matrix is ​​a lithium metal sheet.

[0081] In an embodiment of the present invention, the thickness of the lithium metal sheet is 100-300 μm.

[0082] In a second aspect, the present invention provides a method for preparing a lithium metal negative electrode material, comprising the following steps:

[0083] S1, mixing substance A, compound B1, compound B2, a photoinitiator and an organic solvent to obtain a dispersion;

[0084] Substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg;

[0085] Compound B1 is polyethylene glycol diacrylate (PEGDA);

[0086] The B2 compound includes at least one of vinylene carbonate (VC), ethylene monochloride carbonate (CEC), vinylene sulfate (DTD), and ethylene glycol sulfate (DTD);

[0087] S2, in an inert gas atmosphere, applying the dispersion to the surface of the lithium metal substrate, subjecting the substrate to ultraviolet light polymerization treatment, polymerizing the B1 compound and the B2 compound into an EP compound, and then subjecting the substrate to a standing treatment to obtain a lithium metal negative electrode material.

[0088] Preferably, in the preparation method of lithium metal negative electrode material, the mass ratio of substance A, compound B1 and compound B2 is (10-50): (5-10): (1-5). Exemplarily, the mass ratio of substance A, compound B1 and compound B2 is any value among 10:10:1, 20:8:2, 30:7:3, 40:6:4, 50:5:5 or any value within the range of any two of the above values. Preferably (10-30): (7-9): (1-3). If the proportion of B1 compound and / or B2 compound is too small, the proportion of EP compound obtained by polymerization is too low, and substance A cannot be wrapped, which affects the generation of continuous lithium ion conductive components; if the proportion of B1 compound and / or B2 compound is too large, the ionic conductivity of the functional layer is too low, resulting in increased resistance.

[0089] Preferably, the photoinitiator 、 The mass ratio of B1 compound to B2 compound is (10-50):(5-10):(1-5). Exemplarily, the mass ratio of photoinitiator, B1 compound and B2 compound is any value among 10:10:1, 20:8:2, 30:7:3, 40:6:4, 50:5:5 or any value within the range of any two of the above values. Preferably, (10-30):(7-9):(1-3). When the proportion of photoinitiator is too small, it will affect the polymerization reaction of B1 compound and B2 compound, resulting in a lower degree of polymerization and poorer flexibility of the EP compound; when the proportion of photoinitiator is too large, it will lead to an increase in production costs.

[0090] Preferably, the temperature of the ultraviolet light polymerization treatment is -50°C to -30°C, and the time of the ultraviolet light polymerization treatment is 5 to 15 minutes. Exemplarily, the temperature of the ultraviolet light polymerization treatment is any value among -50°C, -45°C, -40°C, -35°C, and -30°C, or any value within the range of any two of the above values, and the time of the ultraviolet light polymerization treatment is any value among 5 minutes, 8 minutes, 10 minutes, 12 minutes, and 15 minutes, or any value within the range of any two of the above values. In the presence of a photoinitiator, the ultraviolet light polymerization treatment can cause the B1 compound and the B2 compound to be in situ polymerized into the EP compound.

[0091] Preferably, the temperature of the static treatment is 10°C to 30°C, and the time of the static treatment is 10 to 20 hours. Exemplarily, the temperature of the static treatment is any value among 10°C, 15°C, 20°C, 25°C, 30°C, or any value within the range of any two of the above values, and the time of the static treatment is any value among 10h, 12h, 14h, 16h, 18h, 20h, or any value within the range of any two of the above values. The static treatment can ensure that the organic solvent is completely volatilized, and finally a dry lithium metal negative electrode material is obtained.

[0092] In an embodiment of the present invention, the photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO), 1-hydroxy-cyclohexyl-phenyl ketone (HCPK), 4-phenylbenzophenone (PBZ), 2,2-azobis (methylbutyronitrile), benzoyl peroxide (BPO), acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, tert-butyl peroxy-2-ethylhexanoate, and tert-amyl-(2-ethylhexyl) monoester;

[0093] In an embodiment of the present invention, the organic solvent includes at least one of dimethyl ether (DME), N-methyl-2-pyrrolidone (NMP), and N,N-dimethylformamide (DMF).

[0094] In an embodiment of the present invention, substance A is nanoparticles.

[0095] In an embodiment of the present invention, the preparation method of substance A includes: mixing a first salt containing M, ammonium chloride, a second salt containing weak acid radicals and / or organic acid radicals, and a second organic solvent, and subjecting the mixture to ball milling, washing, and vacuum drying to obtain substance A; wherein M is Zn and / or Mg.

[0096] In an embodiment of the present invention, the weak acid radical includes at least one of a silicate radical and an acetate radical.

[0097] In an embodiment of the present invention, the organic acid radical comprises at least one of citrate and lactate.

[0098] In one embodiment of the present invention, the second organic solvent is a mixed solution of water and NMP in any proportion. For example, water and NMP are mixed in a volume ratio of 1:1.

[0099] In another embodiment of the present invention, the second organic solvent is water.

[0100] In an embodiment of the present invention, the rotation speed of the ball milling treatment is 100 to 1000 rpm, and the time of the ball milling treatment is 10 to 20 hours.

[0101] In an embodiment of the present invention, the temperature of the vacuum drying treatment is 50° C. to 120° C., and the time is 1 to 24 hours.

[0102] In a third aspect, the present invention provides a lithium metal negative electrode sheet, which includes the above-mentioned lithium metal negative electrode material and / or the lithium metal negative electrode material prepared by the above-mentioned preparation method.

[0103] In an embodiment of the present invention, the lithium metal negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, and the negative electrode active material layer is the lithium metal negative electrode material provided by the present invention.

[0104] In an embodiment of the present invention, the negative electrode current collector is copper foil.

[0105] In a fourth aspect, the present invention provides a lithium metal battery, which includes the above-mentioned lithium metal negative electrode sheet.

[0106] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.

[0107] The present application has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.

[0108] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.

[0109] The present invention will be further described below in conjunction with embodiments:

[0110] Example 1

[0111] (1) Preparation method of zinc silicate

[0112] ZnCl2 (204.0 mg), NH4Cl (1069.8 mg) and Na2SiO3·9H2O (719.6 mg) were dissolved in 10 mL of a mixed solution of deionized water (DIW) and N-methylpyrrolidone (NMP) (V DIW :V NMP =1:1), and then the solution was transferred to a ball mill and ball-milled at 500 rpm for 12 h to synthesize zinc silicate nanoparticles. The product was washed with deionized water in a centrifuge until the supernatant was neutral, washed three times with ethanol, and dried in a vacuum oven at 60°C for more than 12 h. The product was obtained for use.

[0113] The synthesized zinc silicate is in the state of nanoparticles. With the help of high surface area and strong base and weak acid salt properties, the nanoparticles can attract highly electronegative polymer unsaturated groups in the subsequent artificial SEI construction, thereby changing the distribution state of polymer surface groups in the mixture.

[0114] (2) Construction of artificial SEI film on lithium metal anode

[0115] Take 80 mg of polyethylene glycol diacrylate (PEGDA) and 20 mg of vinylene carbonate (VC) and stir for 1 hour, then add 2 mL of dimethyl ether (DME) and stir for 1 hour. After stirring evenly, add 0.2 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) and 0.2 g of zinc silicate and stir again for 20 minutes to obtain a dispersion.

[0116] In an argon glove box, 15 μL of the dispersion was weighed and evenly applied on the surface of a lithium metal sheet (thickness 200 μm). The lithium metal sheet coated with the dispersion was then placed under a UV lamp for 10 minutes under low dew point (-40°C) conditions to obtain a lithium metal sheet protected by EP@Zn2SiO4. The EP@Zn2SiO4-protected lithium metal anode polymerized by UV light was placed in a glove box at room temperature for 12 hours to allow the DME solvent to completely evaporate, and finally a dry EP@Zn2SiO4-protected lithium metal anode material was obtained, the structural diagram of which is shown in the figure. Figure 1 As shown, the thickness of the functional layer is about 500 nm, and the thickness of the mixed layer is about 50 nm.

[0117] Depend on Figure 2 It can be seen that the EP@Zn2SiO4 artificial SEI (solid electrolyte membrane) prepared by dual in-situ reaction has a dense structure, which can promote uniform deposition of lithium ions and reduce liquid interface resistance.

[0118] Example 2

[0119] The only difference between this embodiment and embodiment 1 is that the 10 mL solvent in step (1) is all deionized water.

[0120] Example 3

[0121] The only difference between this embodiment and embodiment 1 is that in step (2), 0.1 g HMPP and 0.1 g zinc silicate are added.

[0122] Example 4

[0123] The only difference between this embodiment and embodiment 1 is that in step (2), 0.3 g HMPP and 0.3 g zinc silicate are added.

[0124] Example 5

[0125] The only difference between this embodiment and embodiment 1 is that in step (2), zinc silicate is replaced by zinc lactate.

[0126] Example 6

[0127] The only difference between this embodiment and embodiment 1 is that in step (2), vinylene carbonate (VC) is replaced by vinylene sulfate (DTD).

[0128] Comparative Example 1

[0129] The only difference between this comparative example and Example 1 is that in step (2), zinc silicate is not added.

[0130] Comparative Example 2

[0131] The only difference between this comparative example and Example 1 is that in step (2), HMPP, polyethylene glycol diacrylate (PEGDA) and vinylene carbonate (VC) are not added, and no ultraviolet light polymerization treatment is performed, that is, there is no EP compound.

[0132] Battery preparation and performance testing:

[0133] 1. Preparation of batteries:

[0134] (1) Preparation of negative electrode sheet: The lithium metal negative electrode material prepared in the examples and comparative examples was used as the negative electrode active material, and rolled onto a copper foil to prepare a negative electrode sheet. The size of the negative electrode sheet was (100 mm×55 mm).

[0135] (2) Preparation of positive electrode sheet: NCM811 was used as the positive electrode material. The positive electrode material was mixed with conductive carbon black (SP), lithium titanium aluminum phosphate (LTAP) solid electrolyte, polyvinylidene fluoride (PVDF), etc. in a mass ratio of 96:2:1:1, coated on aluminum foil, and made into a positive electrode sheet after drying and pressing. The size of the positive electrode sheet was 96 mm × 51 mm.

[0136] (3) Preparation of diaphragm: PP diaphragm is used as the diaphragm.

[0137] (4) Battery assembly:

[0138] The assembly process adopts soft pack lamination. Lamination: stack the positive electrode sheet, diaphragm, and negative electrode sheet in order to obtain a battery cell. Assembly: heat-press the stacked battery cell and put it into the aluminum-plastic film for top and side sealing. Set the charge and discharge cut-off voltage to 1.0-4.2V, the charge and discharge current to 1A / g, and end the test after 2000 cycles.

[0139] 2. Battery performance test:

[0140] (1) Initial efficiency (first effect) test method:

[0141] First, charge the battery to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then divide the battery into different capacities, charge it to 4.2V at a constant current of 0.33C, and then charge it to I≤0.05C at a constant voltage of 4.2V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, discharge the battery to 1.0V at a constant current of 1C to obtain the discharge capacity C2, and then discharge it to 1.0V at a constant current of 0.1C to obtain the discharge capacity C3, and then discharge it to 1.0V at a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first efficiency) is calculated according to (C2+C3+C4) / (C0+C1)×100%.

[0142] (2) 2000 cycles capacity retention rate test method:

[0143] 1). Take the battery after capacity division, first charge it to 4.2V with 1C constant current, then charge it to I≤0.05C with 4.2V constant voltage;

[0144] 2). After standing for 5 minutes, discharge the battery at a constant current of 1C to 1.0V to obtain the discharge capacity C1;

[0145] 3). Let stand for 30 minutes.

[0146] 4). Repeat steps 1)-3) 1999 times to obtain the discharge capacity C2000; the capacity retention rate after 2000 cycles is calculated according to C2000 / C1×100%.

[0147] Table 1 Battery performance test

[0148] category First effect (%) 2000 cycles capacity retention rate (%) Example 1 87.2 85.1 Example 2 86.8 84.8 Example 3 85.9 82.1 Example 4 87.1 83.9 Example 5 86.8 81.5 Example 6 86.5 78.6 Comparative Example 1 80.1 73.1 Comparative Example 2 72.5 76.7

[0149] It can be seen from the cycle results that compared with comparative examples 1-2, the lithium metal negative electrode material in Examples 1-6 to which substance A (zinc silicate or zinc lactate) and EP compound are added at the same time has the best cycle performance and first effect, indicating that the dual in-situ reaction (including the in-situ redox reaction of substance A and the in-situ polymerization reaction of the EP compound) plays a significant role in protecting the lithium metal negative electrode material.

[0150] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lithium metal negative electrode material, characterized in that: The lithium metal negative electrode material comprises: (a) Lithium metal matrix; (b) a functional layer, the functional layer being disposed on the surface of the lithium metal substrate, the functional layer comprising substance A and EP compound; The substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg; The copolymer monomers of the EP compound include a B1 compound and a B2 compound, wherein the B1 compound is polyethylene glycol diacrylate, and the B2 compound includes at least one of vinylene carbonate, vinyl monochlorocarbonate, and vinylene sulfate.

2. The lithium metal negative electrode material according to claim 1, characterized in that The substance A includes at least one of silicate, acetate, citrate, and lactate; Preferably, the substance A includes at least one of zinc silicate, magnesium silicate, zinc acetate, magnesium acetate, zinc citrate, magnesium citrate, zinc lactate, and magnesium lactate; More preferably, the substance A is zinc silicate.

3. The lithium metal negative electrode material according to claim 1, characterized in that The lithium metal negative electrode material further comprises a mixed layer, wherein the mixed layer is disposed between the lithium metal matrix and the functional layer, and the mixed layer comprises a lithium-philic component, a continuous lithium ion-conducting component and an EP compound; The lithium-philic component includes M metal and Li-M alloy, wherein M is Zn and / or Mg; And / or, the continuous lithium ion conducting component includes a weak acid salt and / or an organic salt of lithium, Li2O and LiOH.

4. The lithium metal negative electrode material according to claim 3, characterized in that In the mixed layer, the mass ratio of the lithium-philic component, the continuous lithium-ion-conducting component and the EP compound is (5-50):(5-50):1; And / or, the lithium-philic component, the continuous lithium-ion-conducting component and the EP compound are combined in such a way that the lithium-philic component and the continuous lithium-ion-conducting component are encapsulated by the EP compound; And / or, the thickness of the functional layer is 20 to 1000 nm; and / or, the thickness of the mixed layer is 10 to 200 nm; And / or, the thickness ratio of the functional layer to the mixed layer is (2-100):(1-20) 。 5. The preparation method according to claim 1, characterized in that: In the functional layer, the mass ratio of the A substance to the EP compound is (1-10):1; and / or, the combination of the substance A and the EP compound is that the EP compound encapsulates the substance A; And / or, the mass of the lithium metal matrix is ​​recorded as n1, the mass of the A substance is recorded as n2, the mass of the EP compound is recorded as n3, and n1, n2, and n3 satisfy the following relationship: 50≤n1 / (n2+n3)≤300.

6. A method for preparing a lithium metal negative electrode material, characterized in that: The steps include: S1, mixing substance A, compound B1, compound B2, a photoinitiator and an organic solvent to obtain a dispersion; The substance A includes a weak acid salt containing M and / or an organic salt containing M, wherein M is Zn and / or Mg; The B1 compound is polyethylene glycol diacrylate; The B2 compound includes at least one of vinylene carbonate, vinyl monochlorocarbonate, vinylene sulfate, and ethylene glycol sulfate; S2, in an inert gas atmosphere, applying the dispersion to the surface of a lithium metal substrate, subjecting the substrate to ultraviolet light polymerization treatment to polymerize the B1 compound and the B2 compound into an EP compound, and then subjecting the substrate to a standing treatment to obtain a lithium metal negative electrode material.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the substance A, the compound B1 and the compound B2 is (10-50):(5-10):(1-5); and / or, the photoinitiator 、 The mass ratio of the B1 compound to the B2 compound is (10-50):(5-10):(1-5).

8. The preparation method according to claim 6, characterized in that: The temperature of the ultraviolet light polymerization treatment is -50°C to -30°C, and the time of the ultraviolet light polymerization treatment is 5 to 15 minutes; And / or, the temperature of the static treatment is 10°C to 30°C, and the time of the static treatment is 10 to 20 hours.

9. A lithium metal negative electrode sheet, characterized in that: The lithium metal negative electrode sheet comprises the lithium metal negative electrode material according to any one of claims 1 to 5, and / or the lithium metal negative electrode material prepared by the preparation method according to any one of claims 6 to 8.

10. A lithium metal battery, characterized in that: The lithium metal battery comprises the lithium metal negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Three-dimensional space chain film-forming additive of electrolyte for lithium-ion battery and preparation method

    CN106532118A

  • Lithium-containing negative electrode and preparation method and application thereof

    CN115440934A

  • Lithium metal negative electrode modified by sustainable flexible protective layer and preparation method of lithium metal negative electrode

    CN116706000A

  • Protective layer modified lithium metal composite negative electrode, preparation method thereof and battery

    CN117096273A

  • Protective film for lithium electrode, and lithium electrode and lithium secondary battery comprising same

    US20180294513A1